Analysis of Attributes That Become Consumer Preferences on Bag Products - Putri, Shafira Mardiani Rizkia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Efve atelier is a local brand from Surabaya which bag is its main product. Several late editions issued a decrease in turnover. One of the main possible reason is the lack of variety of model produced. There are many important attributes that influence consumers when making a purchase. Therefore, this study was conducted to determine the combination of attributes that become consumer preferences for bag products. This research used descriptive quantitative analysis using conjoint analysis. The three attributes obtained from preliminary survey and previous researches are design, color, and material. The three attributes have two levels of each attribute then the stimulus is designed using SPSS software and obtained 8 stimuli. The population of this study are Efve’s consumers and potentiol new consumers with a total of 70 people. The research sample used was 60 people with purposive sampling technique. Based on the results, it is known that the combination of consumer’s prefered attributes for bag products are a combination of warm cool colors, frame bag designs and fabrics. It can also be seen that the attribute that is considered the most important is the color attribute followed by the design and material.